Developing Students’ Essay Writing about Tourism Topics through Word Clustering Technique - Laba, I Nengah (Institut Pariwisata dan Bisnis Internasional, 2017)
This study aimed to analyze the effectiveness of developing students’ essay writing about tourism topics through word clustering technique. The subjects under study were students sitting on semester 6 at Sekolah Tinggi Pariwisata Bali Internasional (International Bali Institute of Tourism). This classroom action research (CAR) was basically triggered by the fact that the subjects under study have still low capability in English essay writing about Tourism Topics. This study made use of pre-test or initial reflection (IR) and post-test research design using descriptive analysis. There were two cycles in this CAR and each cycle consists of four successive sessions. The IR was intended to establish the real pre-existing English essay writing capability of the subject under study. The Mean of the Pre-test or IR score obtained by the subjects under study was 3.63. The Mean of the Post-test or R scores both in Cycle I and in Cycle II showed an increasing figure which is 4.12 in S1, 5.06 in S2, 5.78 in S3, 6.34 in S4, 6.76 in S5, 7.14 in S6, 7.44 in S7 and 7.82 in S8. These figures showed that the Mean of the Post-test or R scores in each session was much higher than the Mean of Pre-test or IR in essay writing. The data analysis further led to the computation of the Grand Mean score for both Cycles I and Cycle II. The computation of the Grand Mean resulted in Cycle I (XI) was 5.32. The computation of the Grand Mean resulted in Cycle II was 7.29. The difference Mean of Cycle I and cycle II is 1.97 (XII – XI = 7.29 – 5.32 = 1.97). These research findings revealed that developing students’ essay writing about the tourism topics through word clustering technique was very effective.